Financialized savings in public water governance: An illustrative case study in the arid American West - Christopher S. Gibson (Finance and Society, 2021)
How does financialization of the economy impact public governance of natural resources? One way includes a shift in how savings and cash accumulation are understood and practiced within public agencies. This article proffers that in the second half of the twentieth century, it became a taken-for-granted understanding that long-term savings should be held in financial investment accounts instead of traditional savings accounts. As a result of this, municipal organizations act as fiscally independent investors, marshaling economic resources to pursue strategic objectives that align with financialized institutional logics. Using a case study of the largest supplier of drinking water in the US, this article examines how the use of financial investments by a major public resource agency, Metropolitan Water District of Southern California, evolved since first establishing an investment policy in the 1940s. Today, this organization maintains investments worth over one billion dollars. Analysis of archival documents suggests that financial activities, even if yielding dwindling returns over time, are counted upon as a source of revenue, deployed to obtain favorable bond ratings, used for access to earmarked funds, and leveraged to acquire land in water-strategic locations. Considering the ubiquity of these financial practices among medium to large-sized municipal governing bodies, the results of this study are suggestive and generalizable across substantive governing fields and in other locations. Ultimately, this study shows that public governance agencies are intertwined with private capital flows, problematizing the oft-assumed distance between public and private actors. The article also interrogates the influence that financial markets have over of public policy, showing that elected governance officials engage in the commodification of money, encouraging the further commodification of environmental resources.
Keywords: 300; Financialization; public policy; water; env ironmental governance; economic sociology